Konsekvenser av rollövertagandet: ”I”, ”me” och individualiteten (Sociologisk Forskning, 2011)
Consequences of role taking: the ”I”, the ”me” and individualityThis paper analyzes the tendency of taking the ”I” and the ”me” in G. H. Meads theory of role taking as two separate, qualitatively different parts of human personality, the ”I” being of individual origin, the ”me” of social. In the original Meadian sense role taking gives rise to both the ”I” and the ”me”. They are dialectically united rather than dualistically separated aspects. They refer to the joint functional power of the subject, finding itself as an object, mediated by the Other. As a consequence, the link between body and the social world becomes theoretically more stringent, as the body is given its place as a cognitive social object among others, this by contrast to interpretations where the body is left as an object mainly outside the human social experience and as a source of agency sui generis, a conception which is in opposition to Meads.The stress on the ”I”-phase, as related to body and concrete action in combination with its direct relation to the ”me”-phase, actualizes Mead as a forerunner in modern biologic/neurologic research on human perceptual, motivational and intentional capacity.Swedish Mead interpreters are critically analyzed. Interpretations of Charon, Giddens, Joas and Habermas are partly scrutinized.The author defines the conceptual pair in terms of activity, subjectivity, temporal relativity and distance.
Keywords: role taking; the ”I” and the ”me”; temporal and spatial distance; dualism – dialectic; subject and object